Chinese Puzzle Molecule: A 15 Hydride, 28 Copper Atom Nanoball1. (5th May 2014) - Edwards, Alison J.; Dhayal, Rajendra S.; Liao, Ping‐Kuei; Liao, Jian‐Hong; Chiang, Ming‐Hsi; Piltz, Ross O.; Kahlal, Samia; Saillard, Jean‐Yves; Liu, C. W.
Abstract The syntheses of the first rhombicuboctahedral copper polyhydride complexes [Cu28(H)15(S2CNR)12]PF6 (NR=NnPr2 or aza‐15‐crown‐5) are reported. These complexes were analyzed by single‐crystal X‐ray and one by neutron diffraction. The core of each copper hydride nanoparticle comprises one central interstitial hydride and eight outer‐triangular‐face‐capping hydrides. A further six face‐truncating hydrides form an unprecedented bridge between the inner and outer copper atom arrays. The irregular inner Cu4 tetrahedron is encapsulated within the Cu24 rhombicuboctahedral cage, which is further enclosed by an array of twelve dithiocarbamate ligands that subtends the truncated octahedron of 24 sulfur atoms, which is concentric with the Cu24 rhombicuboctahedron and Cu4 tetrahedron about the innermost hydride. For these compounds, an intriguing, albeit limited, H2 evolution was observed at room temperature, which is accompanied by formation of the known ion [Cu8(H)(S2CNR)6]+ upon exposure of solutions to sunlight, under mild thermolytic conditions, and on reaction with weak (or strong) acids.